The Evolution of Fasakh in Indonesia and Malaysia: A Legal Comparative Bibliometric Review - Deris Arista Saputra; Zul-kifli Hussin (DIKTUM: Jurnal Syariah dan Hukum, 2025)
Fasakh, a legal mechanism in Islamic family law, allows a wife to seek marriage annulment under specific conditions, differing from talaq, which is initiated by the husband. While both Indonesia and Malaysia recognize fasakh, their legal frameworks differ; Indonesia regulates it under the Compilation of Islamic Law (KHI) with significant influence from customary law (adat), whereas Malaysia enforces it through the Islamic Family Law Enactment, varying across states. This study aims to compare the legal, procedural, and socio-cultural dimensions of fasakh in both countries, employing comparative legal analysis through doctrinal research and bibliometric analysis using VOSviewer to map the evolution of fasakh-related studies from 2018 to 2024. The findings reveal that courts in both jurisdictions acknowledge domestic violence, financial neglect, religious conversion, contagious diseases, and fraud as primary reasons for fasakh, with an increasing recognition of psychological abuse and economic vulnerability as legitimate grounds. This study contributes to comparative Islamic legal scholarship by systematically analyzing fasakh across jurisdictions and introducing bibliometric analysis to trace its scholarly development, identifying emerging trends such as identity fraud, psychological abuse, and digital documentation in marital disputes. Additionally, the study underscores the role of ijtihad in expanding the interpretation of fasakh, aligning it with contemporary maqasid al-shariah (objectives of Islamic law) to ensure justice. Theoretically, the findings highlight the adaptability of Islamic jurisprudence in modern legal contexts, while practically, they provide insights for legal practitioners, policymakers, and religious authorities to enhance judicial consistency and improve access to legal aid for women seeking annulment. This study reinforces the necessity of balancing Islamic legal principles with evolving human rights perspectives, ensuring fasakh remains a protective mechanism within contemporary Muslim societies.